Działalność innowacyjna przedsiębiorstw z wyłącznym udziałem kapitału polskiego na tle przedsiębiorstw z kapitałem zagranicznym - Majewska, Maria; Bator, Paweł (Innovative Activity of Companies with Exclusively Polish Capital Against the Background of the Firms with Foreign Capital, 2006)
In this paper, we analyze the innovation performance of two groups of companies: Polish capital solely companies and firms with foreign capital. The results of our empirical study show that the innovation performance is more characteristic for firms with foreign capital than for firms with Polish capital only. It is also observed that companies with foreign capital collaborate more on innovation with external entities and take more care of the workers' ideas as a potential source of innovation.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1116, s. 112-119